Threading Through Time: Hair Sutures in Plastic and Reconstructive Surgery - Shrinit Babel; Binu Prathap Thomas (Journal of Plastic and Reconstructive Surgery)
Suturing has been a pillar of plastic surgery since its very foundation. From ancient civilizations to modern practices, hair sutures have resurfaced as vital material for wound closure and tissue approximation. This study aimed to explore the historical evolution and application of hair sutures, particularly in facial reconstruction, skin flaps and grafts, peripheral nerve surgery, oral/maxillofacial surgery, and oculoplastic surgery. Notable surgeons and scholars, from Susrata to Sir Harold Gillies, have cited unique properties of horsehair sutures, namely, their pliability, strength, and nonabsorbable nature in various applications. Despite the advent of synthetic materials, recent interest in hair sutures has emerged, driven by their renewable nature and potential for “green” surgical practices. Contemporary studies agree with the historical perspectives, suggesting that hair sutures offer favorable aesthetic outcomes, minimal tissue reaction, and cost-effectiveness. This study illustrates the legacy of hair sutures in plastic and reconstructive surgery.